PROGRAM RATIONALE OF TREATMENT AND PREVENTION IN CHILDREN WITH FREQUENT RESPIRATORY DISEASES - A. V. Deryusheva; I. I. Lvova; N. S. Legotina (LLC "Diagnostics and Vaccines", 2017)
The results of complex clinical and laboratory examination of 146 children aged 2-3 years attending kindergarten were presented. The leading predictors of frequent respiratory disease: disturbance of microbiocenosis oropharyngeal mucosa, immunoglobulins decrease, respiratory allergic pathology were established and scientifically substantiated. The results obtained prove the main directions of therapeutic and preventive measures.